A micro coordinate measuring machine using an active stereovision technique for measuring 3D micro parts *. Issue 1 (July 2017) - Khan, M.U.; Dupont, E.; Al-Hajjar, H.; Mattar, C.; Prelle, C.; Lamarque, F.
Abstract: This paper presents a micro coordinate measuring machine capable to measure and reconstruct three dimensional surfaces of micro parts. The uniqueness of the proposed machine lies in its small foot print with ability to displace micro objects beneath the measuring probe for continuous surface characterisation with micrometer level resolution. Its miniature measuring probe enables its easy integration into several micro applications. In addition, the multiple surface stitching algorithm used in the micro-coordinate measuring machines enhances its capability to reconstruct and measure large 3D surfaces.